ANALYSIS OF FARMERS' ATTITUDES TOWARDS THE IMPLEMENTATION OF CROPPING SYSTEMS RICE FIELD RICE PLANTATION IN SENANING VILLAGE PEMAYUNG DISTRICT - Amelia, Mila; Sativa, Fendria; Jamaluddin, Jamaluddin (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2025)
This study aims to (1) find out the general description of the implementation of the jajar legowo planting system in Senaning Village, Pemayung District, (2) find out the attitude of farmers towards the implementation of the jajar legowo planting system for rice fields in Senaning Village, Pemayung District, (3) find out the relationship between farmer attitudes towards the jajar legowo planting system for rice fields in Senaning Village, Pemayung District. This study was conducted in Senaning Village, Pemayung District. The location was determined intentionally (purposively) with the consideration that in this research area most farmers run rice fields by implementing the Jajar Legowo planting system. The determination of respondents was carried out using the census sampling technique with a total of 62 respondents. The analysis test used was descriptive and non-parametric statistical test with the Chi-Square (x2) method with a contingency of 2 x 2. Based on the results of the study, it was found that the cognitive attitude of farmers had an effectiveness level of 90.3%, an affective attitude of 88.7% and a conative attitude of 88.7%. Which means that the cognitive attitude is higher and is able to influence the affective and conative components. It is concluded that farmers agree with the implementation of the Jajar Legowo planting system for lowland rice fields. This means that there is a real relationship between farmers' attitudes towards the implementation of the jajar legowo planting system for lowland rice fields in Senaning Village, Pemayung District